The Impact of Export Tax Incentives on Export Performance : Evidence from the Automotive Sector in South Africa - Madani, Dorsati H. (2012)
The original goal of the Motor Industry Development Program was to help the automotive industry in South Africa adjust to trade liberalization and become internationally competitive. In simple terms, it consists of an import/export complementation arrangement, whereby the local value-added of components or built-up vehicles exported earns credits that can be used to rebate import duties on components and vehicles. This study provides a first attempt at a quantitative analysis of the Motor Industry Development Program using the difference-in-difference methodology, in order to assess to what extent the program was effective in improving South Africa's automotive export performance during 1996-2006. The authors take a two-tier approach. First, they perform a comparative study using different manufacturing sectors within South Africa; second, they apply this methodology to analyze South Africa and a number of comparator countries that are automotive producers and exporters. The analysis finds that the impact of the program on automotive exports in South Africa is positive and significant. In particular, (i) the largest response to the program in terms of improved manufacturing exports occurs with a delay after the adoption of the law, suggesting that exports need time to fully react to the incentives; and (ii) in turn, the effectiveness of the tax incentives fades in time, reaffirming the common belief that tax incentives may affect some business decisions particularly in the short run, but they are not a primary consideration for investors in the long run.